Ketidakadilan Gender Pada Perempuan Dalam Industri Pariwisata Taman Nasional Komodo - Risdawati Ahmad; Reni Dwi Yunita (Faculty of Social Science, Universitas Negeri Malang, 2019)
This study aims to analyze how gender inequality is against women in the tourism work of the Komodo National Park. The results of this study are expected to be used to evaluate or encourage the implementation of gender-oriented development in order to create more equitable welfare. This research uses a qualitative approach and is conducted on women in Komodo Village, Komodo Island, East Nusa Tenggara. The selection of informants uses purposive sampling technique. Data analysis techniques using the model of Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. The results of the study: 1) women in having limited access to tourism in Komodo National Park, 2) the level of women's participation in tourism work is very low, namely as food sellers at stalls, 3) women's involvement in decision making related to tourism management is still low , 4) men benefit more from the existence of the Komodo National Park compared to women, 5) the forms of gender injustice experienced by women are marginalization and subordination.